Perception of internet addiction among psychiatric residents in an urban area in Indonesia (Medical Journal of Indonesia, 2019)
BACKGROUND In the last two years, many suspected cases of internet addiction have been reported by the media. However, many physicians do not have comprehensive knowledge of internet addiction. Currently, there has been no study conducted among psychiatric residents. This study was aimed to determine the perception of internet addiction among psychiatric residents. METHODS This cross-sectional study was done from April to May 2018. Subjects were recruited by a total sampling method consisting of all psychiatric residents of the Faculty of Medicine, Universitas Indonesia. Perceptions of internet addiction were measured using the illness perception questionnaire revised version for addiction. The calculation of subscales was based on the algorithms available for this instrument. The Mann–Whitney U test was used to determine the association of different years of psychiatric education and the perception of internet addiction. RESULTS Fifty-two subjects completed the survey, and 85% of them reported feeling that they did not have adequate knowledge of internet addiction. They believed that their current knowledge was not sufficient to make diagnosis and management decisions. Junior residents had significantly lower consequence scale scores, with mean (standard deviation) scores of 4.1 (0.54) for juniors and 4.4 (0.48) for seniors (p = 0.021). CONCLUSIONS Psychiatric residents perceived internet addiction as emotionally stressful, understandable, and cyclical, but difficult to control. Senior psychiatric residents had a better perception internet addiction consequences compared with their juniors, who have received only basic knowledge about addiction without clinical exposure, but the perceptions could still be improved.